Romania - Functional Review : Higher Education Sector - World Bank (Washington, DC, 2013)
This review provides a discussion of challenges faced by Romania as a results of reforms, policy changes, growth in enrollment, among others, and provides policy options on how to tackle them. The review focuses on the higher education sector as a whole and how it is managed as a system by the Ministry of Education, Research, Youth and Sport (MERYS). The team assessed how the system is structured, led and managed by MERYS and not how each and every university is structured, led and managed internally. Some internal issues that confront higher education institutions were, however, reviewed since they are common to so many institutions that, by reason of commonality, they deserve to be addressed so that the Ministry can develop appropriate responses. The report includes a large number of findings, conclusions and recommendations. Some of the findings and conclusions require no recommendations. They indicate that the review team is happy with what it found in specific areas and they are included in the report since the team was required to cover these areas and since the team wants to give credit where credit is due. There are other findings and conclusions, indicating areas where improvement is necessary and possible and the team is providing recommendations, but on their own, are not likely to bring about major improvement; then, there are findings and conclusions in areas where the team believes that the potential for the greatest impact lies.